Biomimetic Radical Chemistry and Applications 2021 - Chatgilialoglu, Chryssostomos (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The high importance of free radical chemistry for a variety of biological events, including ageing and inflammation, has attracted considerable interest in understanding the related mechanistic steps at the molecular level. Modelling the free radical chemical reactivity of biological systems is an important research area. When studying free-radical-based chemical mechanisms, biomimetic chemistry and the design of established biomimetic models come into play to perform experiments in a controlled environment, suitably designed to be a similar as possible to cellular conditions. This Special Issue provides readers with a wide overview of biomimetic radical chemistry, where molecular mechanisms have been defined and molecular libraries of products are developed to be used as traces for the discoveries of some relevant biological processes. Several subjects are presented, with five articles and five reviews written by specialists in the fields of DNA, proteins, lipids, biotechnological applications and bioinspired synthesis, with "free radicals" as the common denominator.